Teachers' self-efficacy in dealing with students' online learning difficulties: A study of psychopragmatics in Indonesian language learning - Muhammad Rohmadi; Memet Sudaryanto (Fakultas Sastra Universitas Negeri Malang, 2023)
Efficacy is teachers’ ability to strengthen their self-motivation to help solve learning problems faced by their students. In the learning process, psychopragmatic mastery is expected to strengthen the psychological condition of teachers and students through informative, manipulative, and persuasive sentences so that each student can optimize learning tools to help them achieve learning goals. During the pandemic, it is important to examine teachers’ self-efficacy and psychopragmatics mastery to support students in addressing their online learning difficulties. A qualitative study to investigate these issues was therefore conducted. Participants of this study were teachers from all over Indonesia, consisting of 350 middle and high school teachers. Data were collected through (1) a survey of teacher efficacy during online learning, (2) observations of the forms of efficacy built by the teachers during learning activities and outside the classroom, (3) interviews with the teachers to identify forms of efficacy used to shape students' learning fundamentals. It was found that the teachers tended to increase their efficacy through strong lesson planning. In addition, they often modified learning tools so that the multimedia used could foster enthusiasm and learning motivation for both themselves and the students. The teacher's efficacy in teaching is the key to analysis in psychopragmatic studies because data in the form of snippets of teacher speech can influence student motivation. Psychopragmatics in the teaching and learning process is not only considered the psychology of language that is practiced in learning the Indonesian language, but teachers also have internalized psychological reinforcement in the learning activity that has been planned, implemented, and assessed.Keywords: efficacy, learning difficulties, psychopragmatics, online classEfikasi diri guru dalam menghadapi kesulitan pembelajaran daring siswa: Sebuah studi psikopragmatik dalam pembelajaran bahasa IndonesiaEfikasi adalah kemampuan guru untuk memperteguh motivasi diri sendiri dalam membantu memecahkan masalah belajar yang dihadapi siswanya. Dalam proses pembelajaran, penguasaan psikopragmatik diharapkan dapat memperkuat kondisi psikologis guru dan siswa melalui kalimat-kalimat yang informatif, manipulatif, dan persuasif sehingga setiap siswa dapat mengoptimalkan perangkat pembelajaran untuk membantu mereka mencapai tujuan pembelajaran. Di masa pandemi, penting untuk mengkaji efikasi diri guru dan penguasaan psikopragmatik untuk mendukung siswa dalam mengatasi kesulitan belajar daring mereka. Oleh karena itu, sebuah studi kualitatif untuk menyelidiki masalah ini dilakukan. Partisipan penelitian ini adalah para guru yang tersebar di seluruh Indonesia, terdiri atas 350 guru SMP dan SMA. Pengumpulan data dilakukan melalui (1) survei efikasi guru selama pembelajaran daring, (2) observasi terhadap bentuk efikasi yang dibangun oleh guru selama kegiatan pembelajaran dan di luar kelas, (3) wawancara dengan guru untuk mengetahui bentuk efikasi yang digunakan. untuk membentuk dasar belajar siswa. Berdasarkan data ditemukan bahwa guru cenderung meningkatkan keefektifannya melalui perencanaan pembelajaran yang kuat. Selain itu, mereka sering memodifikasi perangkat pembelajaran agar multimedia yang digunakan dapat menumbuhkan semangat dan motivasi belajar baik bagi diri sendiri maupun bagi siswa. Efikasi guru dalam mengajar menjadi kunci analisis dalam kajian psikopragmatik karena data berupa potongan tuturan guru dapat mempengaruhi motivasi belajar siswa. Psikopragmatik dalam proses belajar mengajar tidak hanya mempertimbangkan psikologi bahasa yang dipraktikkan dalam pembelajaran bahasa Indonesia, tetapi keterampilan guru dalam menginternalisasi penguatan psikologis pada kegiatan pembelajaran yang telah direncanakan, dilaksanakan, dan dinilai.Kata Kunci: efikasi, kesulitan pembelajar, psikopragmatik, kelas daring